1990
DOI: 10.1002/cjce.5450680303
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐Liquid mass transfer in a three‐phase fluidized bed with floating bubble breakers

Abstract: The effects of liquid and gas velocities, particle size and volume ratio of floating bubble breakers to solid particles (V,/v,) on both the volumetric mass transfer coefficient, k,a, and the gas-liquid interfacial area, a, have been determined in three-phase fluidized beds with floating bubble breakers. Beds having a volume ratio (V,/V,) of about 0.15 showed a maximum increase in both k,a and a of about 30% in comparison to that in the corresponding bed without floating bubble breakers. The volumetric mass tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
20
0
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 19 publications
(35 reference statements)
8
20
0
1
Order By: Relevance
“…This is in good agreement with the value obtained in a spoutfluid bed [25] using a non-Newtonian fluid where a value of 0.84 was reported. This is also in qualitative agreement with the dependence on liquid velocity in three phase fluidized beds [24] where they have reported a value of 0.45 whereas others have reported a value of 0.42 [10]. This is also qualitatively similar to the values reported by other authors in bubble columns [31±33].…”
Section: Effect Of Liquid Velocitysupporting
confidence: 93%
“…This is in good agreement with the value obtained in a spoutfluid bed [25] using a non-Newtonian fluid where a value of 0.84 was reported. This is also in qualitative agreement with the dependence on liquid velocity in three phase fluidized beds [24] where they have reported a value of 0.45 whereas others have reported a value of 0.42 [10]. This is also qualitatively similar to the values reported by other authors in bubble columns [31±33].…”
Section: Effect Of Liquid Velocitysupporting
confidence: 93%
“…Assuming liquid axial dispersion is negligible, the plug-flow model [3] (PFM) is generally applied to determine k L a in the distributor (grid zone) of fluidized beds. The axial dispersion model [9] (ADM) improves the PFM by considering liquid dispersion in the axial direction, and thus a certain degree of back-mixing has been taken into account. Alvarez-Cuenca et al [4] observed two well-differentiated mass transfer zones in three-phase fluidized beds with poor mixing in the grid zone but very high mixing in the bulk zone.…”
Section: Discussionmentioning
confidence: 99%
“…Te¯on was used because of its low contact angle with water, hence easier bubble attachment from the sparger ori®ces, low coalescence and small bubbles. Filtered air from the compressed air mains, or nitrogen from a 99.99% purity grade gas cylinder were delivered to the gas distributor through a Gilmont¯owmeter (8). The circulation lines were equipped with globe valves (10), facilitating the experiments and the column had an overow outlet (14) used for adjustment the level of the threephase¯uidized zone.…”
Section: Methodsmentioning
confidence: 99%